Preparation and Evaluation of Oroslippery Tablets Contain Irbesartan and Hydrochlorothiazide Combination for Dysphagia Patients - Yasir Q. almajidi; Yaseen T. Khalaf; Naeem M. Shalan; Israa H. Alani; Wael A. Abu Dayyih (College of Pharmacy University of Baghdad, 2022)
Oro slippery tablets (OSTs) is a technique used to improve swallowing of tablets for patients with dysphagia. The aim of this study was to formulate irbesartan and hydrochlorothiazide as Oroslippery tablets (OST) containing 150 mg irbesartan and 25 mg hydrochlorothiazide for dysphagia patients. A simple and rapid method of analysis was developed and validated according to the ICH guideline using HPLC with UV detector. Tablets were prepared by direct compression and then coated with the slippery coat of three different concentrations of the slippering substance "xanthan gum' (2%, 3% and 4%) in Opadry Colorcone® and evaluated according to USP. Slipperiness test was performed using Albino rabbits. Results showed that 2% xanthan gum gave the shortest swallowing time. Also, disintegration time was increased by the coat significantly with the increase of the gum's concentration in the coat. The release kinetics study of the tested formulations (uncoated versus coated with 2% gum) gave the highest correlation for the "first-order release model" for both drugs in the absence and presence of the slippering agent which indicates that the coating did not interfere with the release kinetics of both drugs.  In a conclusion, 2% xanthan gum as slippering agent the optimum concentration used to promote easy ingestion of this tablet.